Penentuan Jeda Penggantian Komponen Kritis pada Alat Instrumen HPLC (High Performance Liquid Chromatography) di Laboratorium PT. RAA - Retno Aprilia; Septian Rahmat Adnan (Jurnal Optimalisasi, 2020)
PT RAA is one of company that moves in terms of pharmaceutical industry. In the process of checking the quality of pharmaceutical products involving one of the instrumentation namely HPLC (High Performance Liquid Chromatography). The data used in the research is secondary data obtained from the instrument logsheet hplc 2019 2010 than years up to. The method used to determine the critical component is the ABC Classification Method. he critical components of the HPLC instrumentation tool are D2 Lamp L-6585-02 with MTTF value of 277 days, Grating component, Sample Loop Assy with MTTF value of 305 days, and Plunger and Peek Neddle Seal components with MTTF value of 342 days. Calculation of the value of function damage to critical components used the calculation of the selected distribution method, namely Weibull distribution. Optimal ordering for D2 Lamp component L-6585-02 is 2 units / year with 1 unit ordering point, Grating component, Sample Loop Assy is 3 units / year with 1 unit ordering point, and Plunger and Peek Neddle Seal components are 3 units / year with a ordering point of 1 unit.